Letter (copy) - Citrine, Walter, 1887-1983
026-0021-001 International WMC/WJB/MS/1,388 22nd August, 1939. M. Pascual Tomas, Depute, 69, Rue du Taur, Tolouse, FRANCE. Dear Comrade Tomas, I duly received your letter about the possibility of transferring to your wife money that had been sent to you from the International Metal Workers Federation, and have been taking soundings in order to find a way of assisting you in this direction. I have had to approach the Foreign Office again and am awaiting a communication with respect to certain suggestions I have made. Incidentally I may say that I have also brought up the subject of passports again, as of course if these could be obtained and your wife and children restored to you that would be the best thing that could happen. I understand how terrible must be your anxiety about them and am doing all I can to help you here, but there is the opposition of the Nationalist Authorities. I am hoping that some sentiments of humanity will have at last been awakened among some of them. You can rely upon me writing to you immediately I have some definite information to transmit. Yours sincerely, General Secretary. 292/946/26/21